Impact of shell content on compressibility of granular material for land reclamation - Loh, Theresa Lai Teng. (2013)
In Singapore, sand used for land reclamation contains a variable amount of shell content. The amount of shell content will affect the engineering properties of the sand. As the compressive strength of the shell content is much lower than silica sand, a high shell content may adversely affect the densification and compressibility of the granular material. This will lead to settlement problems in the reclaimed land.